2020
DOI: 10.1177/0267658320915501
|View full text |Cite
|
Sign up to set email alerts
|

Investigating L2 writing processes across independent and integrated tasks: A mixed-methods study

Abstract: Most research into second language (L2) writing has focused on the products of writing tasks; much less empirical work has examined the behaviours in which L2 writers engage and the cognitive processes that underlie writing behaviours. We aimed to fill this gap by investigating the extent to which writing speed fluency, pausing, eye-gaze behaviours and the cognitive processes associated with pausing may vary across independent and integrated tasks throughout the whole, and at five different stages, of the writ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(42 citation statements)
references
References 36 publications
0
40
2
Order By: Relevance
“…Another potential limitation of this study concerns the participants' computer skills including the typing style and typing speed were not taken into consideration. As rightly pointed out by Michel et al (2020), the students who are not touch-typists are more likely to lose track of their writing by looking at the keyboard.…”
Section: Limitationsmentioning
confidence: 99%
“…Another potential limitation of this study concerns the participants' computer skills including the typing style and typing speed were not taken into consideration. As rightly pointed out by Michel et al (2020), the students who are not touch-typists are more likely to lose track of their writing by looking at the keyboard.…”
Section: Limitationsmentioning
confidence: 99%
“…Previous work already showed that keystroke data is sensitive to small differences in writing tasks, such as copy writing versus email writing (Conijn et al, 2019). In addition, differences in source usage, such as independent and integrated tasks, have been shown to have an effect on students' pausing and revision behavior (Michel et al, 2020). Therefore, the relationship between keystroke data and writing quality might also differ across tasks.…”
Section: Relation Between Keystroke Data and Writing Qualitymentioning
confidence: 99%
“…Chukharev-Hudilainen et al (2019) quantified L2 writing fluency through time-aligned eye tracking and keystroke logging during English-learners’ online writing. Michel et al (2020) conducted similar work, but added stimulated recalls to the eye tracking and keystroke logging to further investigate learners’ thought processes during fluent and non-fluent writing behaviors, and this time across various writing-task types. Objective methodologies can also be used to investigate the cognitive processes underlying eye tracking, for example, brain-based techniques like event-related brain potentials (ERPs, which are electrophysiologically measured brain responses to external stimuli).…”
Section: Breadth and Depth Of Contemporary Eye-tracking Researchmentioning
confidence: 99%
“…As demonstrated in this special issue, eye tracking, an exquisitely versatile methodology, is an excellent tool to do this because it can show how language users allocate, shift, or divide their attention between multiple channels. Thus, the present special issue features eye tracking used in spoken discourse processing (McDonough et al, 2020), reading-while-listening (Conklin et al, 2020), the visual world paradigm (Andringa, 2020), and in an integrated writing task (Michel et al, 2020). Although the specific research questions in each study differ, the authors share a common interest in how language users integrate multiple sources of information (e.g.…”
Section: Multimodalitymentioning
confidence: 99%
See 1 more Smart Citation